Principles and Applications of Broadband Impulsive Vibrational Spectroscopy - Liebel, M; Schnedermann, C; Wende, T; Kukura, P (American Chemical Society, 2015)
We present an experimental setup for recording vibrational coherences and thereby Raman spectra of molecules in their ground and excited electronic states over the 50-3000 cm(-1) spectral range using broadband impulsive vibrational spectroscopy. Our approach relies on the combination of a andlt;10 fs excitation pulse with an uncompressed white light continuum probe, which drastically reduces experimental complexity compared to frequency domain based techniques. We discuss the parameters determining vibrational coherence amplitudes, outline how to optimize the experimental setup including approaches aimed at conclusively assigning vibrational coherences to specific electronic states, and provide a clear comparison with existing techniques. To demonstrate the applicability of our spectroscopic approach we conclude with several examples revealing the evolution of vibrational coherence in rhodopsin and β-carotene.